(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Youth is the object of economic, scientific-technical, social, political, cultural and spiritual development of the whole society. On the one hand, they constitute the vast majority of the population, on the other hand secondly, young people are ambitious, creative, creativity, creativity, innovation.